Targeting GABA signaling in the tumor microenvironment: implications for immune cell regulation and immunotherapy resistance - Zhao, Yuanqing; Xu, Jin; Yang, Ke; Bao, Li (Frontiers in Immunology, 2025)
As an important inhibitory neurotransmitter, γ-aminobutyric acid (GABA) not only plays a key role in the central nervous system, but also has attracted wide attention in the tumor immune microenvironment in recent years. Studies have shown that tumor cells can synthesize GABA and use it to remodel the tumor microenvironment, thereby promoting the occurrence, development and metastasis of tumors. Although previous studies have revealed the important role of GABA in tumor immune escape, there are still many unknown areas of its mechanism, especially the heterogeneous manifestations in different tumor types and tissue environments. This review summarizes the immunomodulatory mechanisms of GABA in tumor-associated macrophages, CD8+ T cells and dendritic cells in the tumor immune microenvironment, and discusses its potential role in tumor immune escape and immunotherapy resistance, providing new ideas for the development of immunotherapeutic drugs targeting GABA receptors.